2013
DOI: 10.1101/gr.153692.112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of the transcription initiation landscape at single nucleotide resolution during vertebrate embryogenesis

Abstract: Spatiotemporal control of gene expression is central to animal development. Core promoters represent a previously unanticipated regulatory level by interacting with cis-regulatory elements and transcription initiation in different physiological and developmental contexts. Here, we provide a first and comprehensive description of the core promoter repertoire and its dynamic use during the development of a vertebrate embryo. By using cap analysis of gene expression (CAGE), we mapped transcription initiation even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(177 citation statements)
references
References 59 publications
10
167
0
Order By: Relevance
“…Cap-trapping protocols such as CAGE (Carninci et al, 2005) and PEAT (Ni et al, 2010) aim to isolate pol-II mRNA transcripts and sequence the capped ends (TSS tags) with nucleotide resolution. Recent analyses using genome-scale TSS data sets produced with PEAT and CAGE in animal tissues (Ni et al, 2010;Batut et al, 2013;Nepal et al, 2013) have observed that TSSs are not simply located at one or even a few "alternative start site" locations upstream of each pol-II gene. When these TSSs are mapped back to the genome, they distribute spatially in a variety of different "TSS tag clusters" or "initiation patterns."…”
Section: Resultsmentioning
confidence: 99%
“…Cap-trapping protocols such as CAGE (Carninci et al, 2005) and PEAT (Ni et al, 2010) aim to isolate pol-II mRNA transcripts and sequence the capped ends (TSS tags) with nucleotide resolution. Recent analyses using genome-scale TSS data sets produced with PEAT and CAGE in animal tissues (Ni et al, 2010;Batut et al, 2013;Nepal et al, 2013) have observed that TSSs are not simply located at one or even a few "alternative start site" locations upstream of each pol-II gene. When these TSSs are mapped back to the genome, they distribute spatially in a variety of different "TSS tag clusters" or "initiation patterns."…”
Section: Resultsmentioning
confidence: 99%
“…The function of these short and CAGE-sensitive RNAs mapping to internal exons and introns remains elusive. However, these RNA species arise only from a discrete subset of genes and their abundance often does not correlate with the expression of the host gene, arguing against them being merely degradation intermediates [37,38].…”
Section: Cap Analysis Of Gene Expression (Cage)mentioning
confidence: 99%
“…Lack of this 5'-most exon in differentiated myotubes could contribute to the increased Cryab protein production. 120,121 Because alternative TSS usage is common during vertebrate embryogenesis 122,123 and in different cell types, [124][125][126][127] such a transcription-based control of uORF regulation could have broad implications in developmental regulation of gene expression.…”
Section: Uorfs As Widespread Repressive Genetic Elementsmentioning
confidence: 99%